Question
upstudy study bank question image url

In Exercises \( 37-40 \), find three solutions to the system of equations, 37. \( \left\{\begin{array}{r}x+2 y+z=5 \\ y+3 z=9\end{array}\right. \) 38. \( \left\{\begin{array}{r}x+5 y+3 z=9 \\ 2 x+9 y+7 z=5\end{array}\right. \) 39. \( \left\{\begin{array}{r}x+7 y-3 z=8 \\ z=5\end{array}\right. \) 40. \( \left\{\begin{array}{r}x \\ y-3 z=7\end{array}\right. \)

Ask by Bob Frazier. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are three solutions for each of the four systems: **Exercise 37:** 1. (−13, 9, 0) 2. (−8, 6, 1) 3. (−3, 3, 2) **Exercise 38:** 1. (−56, 13, 0) 2. (−64, 14, 1) 3. (−48, 12, −1) **Exercise 39:** 1. (23, 0, 5) 2. (16, 1, 5) 3. (9, 2, 5) **Exercise 40:** 1. (0, 7, 0) 2. (1, 10, 1) 3. (−2, 4, −1) Each set satisfies the respective system of equations.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

To find solutions to the systems of equations, we can derive values for the variables step by step. For system 37: 1. From the second equation \( y + 3z = 9 \), we can express \( y \) in terms of \( z \): \[ y = 9 - 3z. \] 2. Substituting \( y \) into the first equation gives: \[ x + 2(9 - 3z) + z = 5 \implies x + 18 - 6z + z = 5 \implies x - 5z = -13 \implies x = 5z - 13. \] 3. Choosing \( z = 0, 1, 2 \), we can get: - \( z = 0 \): \( y = 9 \), \( x = -13 \) ⇒ Solution: \( (-13, 9, 0) \). - \( z = 1 \): \( y = 6 \), \( x = -8 \) ⇒ Solution: \( (-8, 6, 1) \). - \( z = 2 \): \( y = 3 \), \( x = -3 \) ⇒ Solution: \( (-3, 3, 2) \). For system 38: 1. We can solve the equations simultaneously. From second equation, express \( 2x+9y+7z=5 \) in terms of one variable: - From first equation \( x = 9 - 5y - 3z \). 2. Substitute \( x \) into the second equation: \[ 2(9 - 5y - 3z) + 9y + 7z = 5 \implies 18 - 10y - 6z + 9y + 7z = 5 \implies -y + z = -13 \implies y = z + 13. \] 3. Choose values for \( z \): - \( z = 0 \) ⇒ \( y = 13 \) ⇒ \( x = -6 \) ⇒ Solution: \( (-6, 13, 0) \). - \( z = 1 \) ⇒ \( y = 14 \) ⇒ \( x = -7 \) ⇒ Solution: \( (-7, 14, 1) \). - \( z = 2 \) ⇒ \( y = 15 \) ⇒ \( x = -8 \) ⇒ Solution: \( (-8, 15, 2) \). For system 39: 1. Substitute \( z = 5 \) directly into first equation: \[ x + 7y - 3(5) = 8 \implies x + 7y - 15 = 8 \implies x + 7y = 23 \implies x = 23 - 7y. \] 2. Choose different values for \( y \): - \( y = 0 \) ⇒ \( x = 23 \) ⇒ Solution: \( (23, 0, 5) \). - \( y = 1 \) ⇒ \( x = 16 \) ⇒ Solution: \( (16, 1, 5) \). - \( y = 2 \) ⇒ \( x = 9 \) ⇒ Solution: \( (9, 2, 5) \). For system 40: 1. Solve \( y - 3z = 7 \) for \( y \): \[ y = 7 + 3z. \] 2. Assign different values to \( z \): - \( z = 0 \) ⇒ \( y = 7 \) ⇒ Solution: \( (x, 7, 0) \) for any \( x \). - \( z = 1 \) ⇒ \( y = 10 \) ⇒ Solution: \( (x, 10, 1) \) for any \( x \). - \( z = 2 \) ⇒ \( y = 13 \) ⇒ Solution: \( (x, 13, 2) \) for any \( x \). Feel free to plug in any x-value you desire for systems 40! Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy